2022
DOI: 10.1093/cid/ciac949
|View full text |Cite
|
Sign up to set email alerts
|

Weight and Metabolic Changes After Switching From Tenofovir Alafenamide/Emtricitabine (FTC)+Dolutegravir (DTG), Tenofovir Disoproxil Fumarate (TDF)/FTC + DTG, and TDF/FTC/Efavirenz to TDF/Lamivudine/DTG

Abstract: Participants randomised to first-line tenofovir alafenamide (TAF)/emtricitabine (FTC)+dolutegravir (DTG), tenofovir disoproxil fumarate (TDF)/FTC+DTG or TDF/FTC/efavirenz (EFV) for 192 weeks were then switched to TDF/lamivudine (3TC)/DTG for 52 weeks. Participants switching either TAF/FTC+DTG or TDF/FTC/EFV to TDF/3TC/DTG showed statistically significant reductions in weight, low density lipoprotein, triglycerides, glucose and glycated haemoglobin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 10 publications
2
25
2
Order By: Relevance
“…Our findings are supported by data from the CHARAC-TERISE study, in which a subset of participants originally randomized to either TAF/FTC/DTG, TDF/FTC/ DTG or TDF/FTC/EFVas part of the ADVANCE study [10] were all switched to TDF/3TC/DTG showing only modest decreases in weight after this switch [11].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Our findings are supported by data from the CHARAC-TERISE study, in which a subset of participants originally randomized to either TAF/FTC/DTG, TDF/FTC/ DTG or TDF/FTC/EFVas part of the ADVANCE study [10] were all switched to TDF/3TC/DTG showing only modest decreases in weight after this switch [11].…”
Section: Discussionsupporting
confidence: 74%
“…Median time between start TAF/INSTI and first recording of at least 7% weight gain was 12 months (IQR [6][7][8][9][10][11][12][13][14][15][16][17][18] and time between first recording of at least 7% weight gain and discontinuation of TAF and/or INSTI was 18 months . This did not differ between groups, when stratified by discontinued agent (Table 1).…”
Section: Study Populationmentioning
confidence: 99%
“…12 Recent studies of switch from EFV to DTG while maintaining other ART components have ranged from a mean 1-year weight gain of 1.1 kg in Zambia 10 to 2.9 kg, nearly 3-fold greater, in South Africa. 11 With recent widespread transition to DTG/TDF/3TC, it is important to understand effects on weight and metabolic disease across different populations and contexts throughout sub-Saharan Africa.…”
Section: Introductionmentioning
confidence: 99%
“…10 Another study in South Africa showed that switch from TAF to TDF resulted in weight loss in women, but not in men, highlighting potential sex-specific effects. 11 Switch from EFV to DTG also may also lead to weight gain, albeit with variable effects in different populations that could be due to heterogeneity in food environment or genetic polymorphisms affecting drug metabolism. 12 Recent studies of switch from EFV to DTG while maintaining other ART components have ranged from a mean 1-year weight gain of 1.1 kg in Zambia 10 to 2.9 kg, nearly 3-fold greater, in South Africa.…”
Section: Introductionmentioning
confidence: 99%
“…(7) Blood pressure rises with age, so any monitored cohort will see a natural rise. (8) Even if there is a difference in the risk of hypertension between dolutegravir and efavirenz, or between TAF and TDF-based treatment [31], this may not be sufficient reason to change treatment. Hypertension can be monitored and treated using cheap generic drugs.…”
Section: Issues With Interpretation Of Hypertension In Clinical Trialsmentioning
confidence: 99%